2012
DOI: 10.1007/s10310-011-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of management and spatial characteristics on plant species richness of Castanea sativa Mill. woodlots in the NW Iberian Peninsula

Abstract: This paper analyzes the effect of the spatial characteristics and intensity of land use on vascular plant species richness in Castanea (Chestnut) woodlots of the northwestern Iberian Peninsula included in the category ''9260 Castanea sativa woodland'' (Annex I, DC 92/43 European Community). Digital maps were used to characterize 30 woodlots for which land use intensity was estimated and all plants found were inventoried. The results show that woodlot shape and land use intensity have a significant effect on va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…The full abandonment of chestnut stand cultivation does not automatically induce higher plant diversity, and the management intensity modulates the effect on species richness (Guitián et al 2012). However, lower levels of species richness do not mean lower quality of biodiversity (Boncina 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The full abandonment of chestnut stand cultivation does not automatically induce higher plant diversity, and the management intensity modulates the effect on species richness (Guitián et al 2012). However, lower levels of species richness do not mean lower quality of biodiversity (Boncina 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, several studies have shown their high ecological importance in supporting a wide variety of flora and fauna (e.g. Gondard & Romane 2005;Gondard et al 2006;Pezzi et al 2011;Guitián et al 2012;Zlatanov et al 2013). However, actual actions for preserving stand-scale biodiversity of chestnut coppices are, to a certain extent, often neglected by forest managers, even when stands are located within landscapes of recognized naturalistic value and/or designated for conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…They all have a mixed diet in which fruits represent an important fraction from the end of the summer to the middle of the winter in the north of Spain (Guitia´n et al 2000).…”
Section: Species Studiedmentioning
confidence: 99%
“…Its fruits can measure 7-12 mm and weigh 130-150 mg (Peterken and Lloyd 1967), and are consumed mainly by birds (Guitia´n et al 2000).…”
Section: Species Studiedmentioning
confidence: 99%
“…These open stands (known in NW Spain as soutos, castañeros or castañeos) are found close to small villages and usually include very old, large chestnuts trees (more than 150 years old and breast diameter more than 40 cm) growing at low densities (<400 stems/ha). Although man-made, these AFS are included in the Habitats Directive (Directive 92/43 Annex 1: "Castanea sativa woodlands"; EC, 1992) and show a high species richness for moderate intensity of use (Guitián et al, 2011). Some coppice stands devoted to traditional chestnut production have been almost totally abandoned, and most stands were destined for production of high quality timber and biomass (Menéndez-Miguélez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%